A full scale bicycle aerodynamics testing methodology - Chowdhury, H.; Alam, F.; Mainwaring, D. (Procedia Engineering, 2011)
Aerodynamically efficient sport equipment/accessories and athlete's body postures are considered to be the fundamental aspect to achieving better outcomes. Like any other speed sports, the aerodynamic optimization is essential in cycling. A standard full scale testing methodology for the aerodynamic optimization of a cyclist along with all accessories (bicycle, helmet, cycling suit, shoes, goggle, etc.) is not well developed and standardized. This paper describes a design and development of a full scale testing methodology for the measurement of aerodynamic properties as a function of cyclist's body positions along with various accessories under a range of wind speeds. The experimental findings indicate that the developed full scale testing methodology can be used for the aerodynamic optimization of all cycling events.